Safety Risk and its Impact to the Risk Management System in the Construction Industry at National Capital Region Philippines - Joble, Jhonmonawel C; Briones, Jesus P. (International Journal of Economics, Business and Management Studies, 2022)
This descriptive-quantitative type of study identified how safety risks impact the risk management system of the construction industry in the National Capital Region, Philippines. A researcher-structured survey questionnaire was made to gather the needed data for this study and was distributed to different construction sites' key personnel like the project in-charge, project manager, and safety officer with either the use of Google form or by the conventional method which is a printed questionnaire directly distributed to the project sites. The collected data were analyzed utilizing frequency, percentage, weighted mean, standard deviation, and T-test. The findings indicated that the key personnel were familiar with the existing rules and laws in terms of construction safety that are being implemented in the country, however there are some common safety practices which were not properly implemented. It was also found that the rewards system will help improve the company’s safety implementation even with less supervision. The study also found out that mitigating safety risks in the construction sites is still an area of concern in the project risk management system. Since there were still some lapses in implementing safety protocols, the main goal of a risk management system which is to minimize the risks cannot be attained until safety protocols are properly implemented in every project site. To control and mitigate safety risks in the workplace, a comprehensive risk management plan which contains different levels of safety controls should be developed and implemented.